Analisis Tingkat Kepuasan Penghuni Asrama terhadap Fasilitas, Biaya dan Pelayanan Yang Diberikan (Studi Kasus pada Rusunawa YPSBR Muara Bulian) - Ahmad Fithoni; Azman Azman (CITRA EKONOMI, 2021)
The purpose of this study was to determine and analyze the level of satisfaction of the residents of the Rusunawa YPSBR dormitory in terms of the facilities, prices and services provided. The research was conducted by surveying the residents who were also respondents in the study as many as 20 people. The results showed that the condition of the facilities provided was included in the adequate category with an index of 4.18, while the price offered was classified as very cheap with an index of 4.52 and for the services received by residents it was classified as good with an index of 3.96. For the level of occupant satisfaction on the three variables studied, the results showed that residents were satisfied with the management carried out with an index of 3.97, where residents were very satisfied with the price set because it was cheaper than other places while facilities and services were still considered ordinary and the same as anywhere else.